Legal Views of UIN Antasari Lecturers on The Increase In Cooking Oil Prices - Nurul Hikmah; Dr. Hj. Rabiatul Adawiyah, M. Ag; Muhammad Fahmi Nurani, SEI. MH (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
An interesting problem in this study discusses the increase in cooking oil raw materials. Cooking oil itself can be said to be scarce in October 2021-March 2022. This scarcity has caused the price of cooking oil to rise in the market. This study aims to find out how the opinions of economics lecturers on the causes of the increase in cooking oil prices. and to find out how the strategy is carried out in dealing with this increase, as well as to find out how the increase in cooking oil is in the perspective of sharia economic law. This type of research uses qualitative methods with field research with a qualitative approach and uses observation and interview methods, with informants in this study totaling 8 economic lecturers at UIN Antasari Banjarmasin, namely at the Faculty of Sharia, Faculty of Economics and Islamic Business and Faculty of Da'wah and Communication Sciences. The results of the research conducted by researchers show that there are differences of opinion among economics lecturers regarding the increase in cooking oil prices in October 2021-March 2022. Five economics lecturers stated that it was due to hoarding. Three other economics lecturers stated that it was due to inflation. When viewed from the perspective of sharia economic law, the increase in cooking oil prices is due to inflation, the legal basis used is (H.R Abu Dawud No. 345 and Ibn Majah No. 2200) then it is a natural and permissible thing, but if it is due to hoarding then it is not allowed in Islam. The strategy carried out by the government is to find new alternatives to cooking oil, the government must limit the export of cooking oil abroad, and also oil must be subsidized by the government.